Implementation strategies for web-based applications for screening : a scoping review - Ooi, Chor Yau; Ng, Chirk Jenn; Sales, Anne E.; Lim, Hooi Min (2019)
Introduction: Screening is an effective primary prevention strategy in healthcare. However, uptake of screening remains low. Many strategies have been developed and found to be effective in increasing uptake of screening including using web-based applications (web-apps). However, not much is known about effective implementation of web-apps for screening in the real-world setting. Objectives: This scoping review aimed to identify (1) implementation strategies to implement web-apps for screening; (2) implementation frameworks used for implementing web-apps for screening; (3) outcome measures of implementation strategies and (4) implementation strategies that were effective. Method: This scoping review was conducted based on Arksey O’Malley’s framework. After identifying the review question, two researchers independently screened and selected relevant literature from PubMed, Embase, Cochrane, CINAHL, PsycINFO, ISRCTN registry, OpenGrey, ClinicalTrials.gov, World Health Organization International Clinical Trials Registry Platform and Web of Science. This was followed by charting of the data using a standardized form. Finally, a researcher collated, summarised, and reported the results quantitatively and qualitatively based on the review objectives. Results: 16476 studies were retrieved where 5669 were duplicates. From a total of 10807 studies, 10784 studies were excluded based on screening of title and abstract. Twenty-three full-text articles were reviewed and 4 articles were included in the final analysis. Many studies were excluded because they did not focus on implementation of web-apps. Facilitation was the most cited implementation strategy used followed by reminders, clinical champions, educational meetings and materials. Only 2 studies used implementation frameworks to guide the evaluation of their studies. Common outcome measures for implementation strategies were feasibility, fidelity and penetration. Implementation strategies reported to be effective were quality improvement meetings, facilitation, educational meetings and clinical champions. Discussion/ Conclusion: There is a dearth of literature on implementation of web-apps for screening and therefore there is a need to conduct more research in development and evaluation of implementation of web-apps screening interventions.